An Overview: A Design Strategy for Dioxide Carbon QCM Gas Sensor Based on MOFs or COFs - Xukun Wang; Tong Zhang (Advanced Sensor Research)
Abstract The quartz crystal microbalance (QCM) platform is a high‐performance sensor device in which the change in the characteristic quantity of the sensor does not depend on the difference in the electrical amount of the sensitive material but is related only to the adsorption capacity of the exposed material. Metal–organic frameworks (MOFs)/covalent–organic frameworks (COFs), as a functional material, have unique physical and chemical properties and are capable of trapping and adsorbing gases in large quantities. QCM gas sensors based on MOFs or COFs have a promising application in CO2 gas sensing. This work summarizes the current research on CO2 sensors and the current problems and challenges. Different improvement strategies are concluded for gas sensors' core “4S” characteristics, that is, sensitivity, selectivity, response speed, and stability. To provide some ideas and suggestions for the future development of MOFs/COFs‐based QCM carbon dioxide gas sensors.